2023
DOI: 10.19160/e-ijer.1155362
|View full text |Cite
|
Sign up to set email alerts
|

Children's Sense of Humor and Humor in The Classroom

Abstract: The purpose of this study is to identify the lesson in which primary school students laugh the most and why they laugh in this lesson. For this purpose, the study was carried out according to the parallel design (Quantitative Data [Collection + Analysis] + Qualitative Data [Collection + Analysis]  Association  Interpretation) which was one of the mixed method research designs. The study group consisted of 227 primary school students (2-4th grade). The quantitative data of the study were collected through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…According to this value, which can vary between 0-1, it can be said that children's appreciation of the value of humor is at a moderate level. In Yalçıntaş & Kartal's (2023) study, similar to the findings of this study, it was found that the average humor understanding scores of primary school students were at a medium level. Humor is a skill that can be developed, taught and learned (Lyon, 2006).…”
Section: Discussion and Resultssupporting
confidence: 88%
“…According to this value, which can vary between 0-1, it can be said that children's appreciation of the value of humor is at a moderate level. In Yalçıntaş & Kartal's (2023) study, similar to the findings of this study, it was found that the average humor understanding scores of primary school students were at a medium level. Humor is a skill that can be developed, taught and learned (Lyon, 2006).…”
Section: Discussion and Resultssupporting
confidence: 88%